A comparative study of mangroves in degraded, natural, and restored ecosystems in Guyana. Issue 2 (3rd April 2022) - Dookie, Sabrina; Jaikishun, Sirpaul; Ansari, Abdullah Adil
ABSTRACT: Mangrove ecosystems are subject to multiple environmental stresses which often challenge their resistance and resilience. In this study, comparisons were made between mangrove trees and seedlings in natural, degraded, and restored mangrove ecosystems found on the coastline of Guyana. Biophysical measurements were made using the point-centred quarter method (PCQM) in both the wet and dry seasons. The density of seedlings and trees varied between locations, with natural mangrove ecosystems having the highest density while degraded ecosystems had the lowest. Significant differences were also reported for biophysical measurements for seedlings (df = 5, p < 2.2e-16) and trees (height; diameter at breast height) [F(10, 564) = 112.47, p < 2.2e-16] between all three types of mangrove ecosystems with biophysical measurements showcasing positive correlations (p < .05, rs  < 0.5) in most locations. Regression analysis results further established strong relationships between biophysical measurements of plants and their locations. Key policy insights: Mangrove ecosystems provide several ecological goods and services while providing protection against the sea and sustaining the resident biodiversity. There is a need for greater conservation and preservation efforts for mangrove ecosystems since their dynamics are heavily impacted by anthropogenic activities and natural phenomena. Mangroves have the capacity to capture and store carbon, making them active participants in the global sequestration of carbon, and in the fight against climate change.